Kebijakan Hilirisasi Nikel dan Arus Investasi Asing Terhadap Kesejahteraan Daerah: Studi Kasus Provinsi Sulawesi Tenggara - Pandin, Evelyn Gracia Ranita; Arumdita, Hanna Monika (Jurnal Transformasi Global, 2026)
Southeast Sulawesi is a region of opportunities and challenges. As one of the richest nickel resources in Indonesia, this region has been receiving massive Foreign Direct Investment (FDI) from Chinese industrial companies, aiming to boost their prominent automotive industry’s productivity through an affordable and sustainable source of extraction. In response to this demand, the Government of the Republic of Indonesia released a national downstreaming regulation to enhance the nation’s capacity for producing value-added products, thereby contributing to the global supply chain. This research, employing a descriptive analytical method, has found that multiple factors influence the dynamics of local society, which creates an intersection of international and domestic scope of the issue (intermestic). In terms of economic productivity, this research has also found that the policy has proven to gradually boost its growth. However, layered sociocultural issues persist. This research utilised the perspective of liberalism, especially the concept of globalisation and interdependence, while assessing the possible multiplier effect as a result of a policy implementation. Data collection includes completing multiple interviews and library research, aiming to cross-check and verify findings. The purpose of this research is to offer an analysis of Indonesia’s downstreaming policy implementation and its effects in ensuring a secure future for the nation in the midst of global uncertainty.